Leptin, adiponectin, and short-term and long-term weight loss after a lifestyle intervention in obese children - Siegrist, Monika; Rank, Melanie; Wolfarth, Bernd; Langhof, Helmut; Haller, Bernhard; Koenig, Wolfgang; Halle, Martin (Nutrition, 2013)
Objective: In overweight children, high leptin levels are independently associated with higher risk for cardiovascular disease, whereas adiponectin seems to be protective against type 2 diabetes and atherosclerosis. The study examines the predictive value of leptin for weight loss after a 4- to 6-wk inpatient therapy and again after 1 y; as well as the association among weight loss, leptin, and adiponectin levels and changes in cardiometabolic risk factors after therapy. Methods: Body mass index (BMI), blood pressure, Tanner stage, and cardiometabolic risk factors were studied in 402 children (59.2% females, 13.9 ± 2.3 y, BMI 33.8 ± 5.7 kg/m2) before and after a 4-to 6-wk inpatient intervention (exercise, diet, and behavioral therapy) and BMI 1 y later (n = 206). Results: BMI was reduced from 33.8 ± 5.7 to 30.5 ± 5.1 kg/m2 (P < 0.001) during the lifestyle intervention and remained unchanged after 1 y. Baseline BMI was positively associated with leptin (r = 0.60; P < 0.001) and cardiometabolic risk factors (blood pressure, high-density lipoprotein [HDL] cholesterol, triglycerides). Baseline leptin was associated with BMI and triglycerides (r = 0.39; P < 0.001), baseline adiponectin with HDL-cholesterol (r = 0.40; P < 0.001). Baseline BMI explained 40.7% of the variance in weight loss during therapy. The combination of BMI, sex, and leptin explained 50.4% of the variance. Neither BMI nor leptin predicted weight changes over the long term. Conclusions: Overweight children maintained a substantial amount of weight loss after participation in a short-term inpatient lifestyle intervention. Baseline BMI was positively associated with weight reduction during the intervention, whereas baseline leptin had only a minor predictive value. © 2013 Elsevier Inc.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Adipokines; Adolescents; Cardiometabolic risk; Inpatient weight loss program